Improvement of the technique of technical and tactical training of taekwondists-juniors - Романенко Вячеслав Валерійович (Vyacheslav Romanenko); Нехтялов Едуард Андрійович (Eduard Nekhtyalov) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to improve a technique of technical and tactical training of taekwondists-juniors. Material and methods: theoretical analysis and generalization of scientific and methodical literature, pedagogical supervision of educational and training classes and competitions, pedagogical testing, pedagogical experiment, methods of mathematical statistics. Results: a complex of special exercises is developed for the increase of the level of technical and tactical preparedness of taekwondists-juniors, practical recommendations are prepared. Conclusions: features of the performance of the most demanded technical and tactical connections in a fight of taekwondists-juniors are defined, significant correlation interrelations between the levels of technical and tactical and special physical fitness are revealed, results of the mathematical analysis testifies that the offered innovations authentically (р<0,05) promote the improvement of the level of technical and tactical preparedness of taekwondists-juniors.